Attitude of the Polish Society to the Covid-19 Pandemic Restrictions in the Tourism Industry - Dawid BORUCINSKI; Agnieszka MROCZEK-CZETWERTYNSKA; Paula PRZYSADA-SUKIENNIK (Communications of International Proceedings, 2021)
The COVID-19 pandemic has had a significant impact on all areas of human life, both socially and economically. This paper aims to determine how the different age groups perceived the COVID-19 pandemic restrictions implemented in the tourism (hospitality) industry. The basis for the analysis was a survey conducted in May 2021 on the perception and impact of COVID-19 restrictions on Polish society. The research was performed on a representative sample of 1000 people, with a statistical error of 3%. The study showed a strong correlation between the age of the respondents and the acceptance of restrictions. The elderly treated the restrictions as more justified, as opposed to younger respondents.
Keywords: Tourism Industry; Pandemic Restrictions; COVID-19.